Strategic Readiness : the making of the learning organization - Redding, John C. (Jossey-Bass San FranciscoUS, 1994)
Shows how organizations learn as they plan, implement and modify business strategies; and explains how they prepare to learn. Presents the three phases of the strategic learning cycle namely: continuous planning, improvised implementation, and deep reflection. Details the actions which learning organizations take to accelerate the strategic learning process. Some of these actions include: heightening strategic awareness, making learning a way of life; and becoming self-organizing.